3x+12x-6=3(5x+7)

Simple and best practice solution for 3x+12x-6=3(5x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+12x-6=3(5x+7) equation:


Simplifying
3x + 12x + -6 = 3(5x + 7)

Reorder the terms:
-6 + 3x + 12x = 3(5x + 7)

Combine like terms: 3x + 12x = 15x
-6 + 15x = 3(5x + 7)

Reorder the terms:
-6 + 15x = 3(7 + 5x)
-6 + 15x = (7 * 3 + 5x * 3)
-6 + 15x = (21 + 15x)

Add '-15x' to each side of the equation.
-6 + 15x + -15x = 21 + 15x + -15x

Combine like terms: 15x + -15x = 0
-6 + 0 = 21 + 15x + -15x
-6 = 21 + 15x + -15x

Combine like terms: 15x + -15x = 0
-6 = 21 + 0
-6 = 21

Solving
-6 = 21

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x-1/8=15/8 | | 16-2t=3t+9 | | x-1/8=15/8= | | 12a-17=9 | | -2p=9 | | -10w+1=25 | | 4x+y-2=16 | | 81-y+6y+4+8y-18=180 | | -4(5x-12)= | | 2k-12=4 | | 22.5=3y | | 2x+1-3x-5= | | 24x+19=3(6x+8)+6x-5 | | 7g+14=8g+5 | | 4x+3=4y+1 | | .3x-1.6=.5 | | 4x+3=4y-1 | | 1-6x=8-7-3x | | 27x^2-75x+28=0 | | 9(2x-9.5)=-16.5x+8x | | 25=-5/6y | | 122/3/2 | | -6.47-16.4g=7.53-12.4g | | 4.99-10.9t=-1.17+4.5 | | 25x-30=370 | | 15+8y=47 | | -2.6b-1=18.25-1.5b | | -4.3g=-2.7g+17.6 | | 4x+20x-9=6(4x+6) | | 10=-x-2y | | (9+3)(9+5)=0 | | 5/3x-2=x-6 |

Equations solver categories